70 Years of Popeye - Lively, Zachary (USA Winstar, 2000)
Everyone's favorite squinty-eyed, spinach-chompin' sailor is back in this collection of 12 animated classics, which are quite humorous and, in typical Popeye fashion, strong to the finish. The cartoons have been digitally restored with enhanced picture and sound, and feature new sound effects delightfully mixed with original dialogue. The color and texture are as bright and as clear as they would have been at their original theatrical release. All the familiar characters--Bluto, Olive Oyl, Wimpy--make appearances and prove that certain antics never fail to entertain, even decades after their introduction. Favorite episodes such as "Popeye for President" and "Taxi Turvy" retain their brilliance and inventiveness and can run side by side with today's cartoons. Also included is the epic "Popeye the Sailor Meets Ali Baba and the Forty Thieves," which both spoofs and honors the fantastic live-action desert adventures popular at the time of its release. The tape itself is bookended by clips featuring Popeye at an awards dinner populated by famous stars of stage and screen. This is highly appropriate, for, as this collection attests, he remains one of the classic characters of the silver screen
Language : English Subtitles : No Subtitles
Keywords: Animation